Chrysanthemum - Henkes, Kevin (New York : Greenwillow Books, 1991)
Chrysanthemum loves her name until she starts going to school and the other children begin to make fun of it.
Wilson's Children, October 2010.
Elem. School Library Collection, March 1998.
School Library Journal, September 1996.
Five Owls, January 1997.
Book Links (A.L.A.), January 2004.
Book Report, March 1995.
Keywords: Names, Personal -- Juvenile fiction; Schools -- Juvenile fiction; Names, Personal -- Fiction; Schools -- Fiction